EMPATI DAN PEMAAFAN PADA MAHASISWA FAKULTAS PSIKOLOGI UIN SUSKA RIAU - Lestari, Dwi Indra; Agung, Ivan Muhammad (Jurnal Studia Insania, 2016)
Forgiveness has one important in human interpersonal relation.The purpose of this study was to examine the relationship between empathy and forgiveness on undergraduate student. The participants undergraduate student were 309 (47: men, 262, women) from faculty of Psychology UIN Suska Riau.  This research used two kinds of scale, empathy  and forgiveness scale.The result showed: there is a significant and positive correlation  between empathy and forgiveness.. The  Implication of this result are discussed on the interpersonal relation contexts.